Hydraulic performance of a pre-aerated stilling basin: Experimental study - Yu Zhou; Tengzhi Huang; Ke Xu; Jiakai Mei; Siwei Jia; Qiaoni Yu; Jinglin Qian (PLoS ONE, 2025)
Spillway chutes are critical in dam flood control, particularly in high dams where high water heads and large discharge in narrow canyons amplify the demand for safe discharging. For large unit discharges in spillways, aeration protection is essential to prevent cavitation erosion, but challenges arise from air duct choking in the traditional spillway and nonaerated regions in the stepped spillway. This paper introduces a novel spillway called the pre-aerated stilling basin spillway (PSBS). The primary distinction between PSBS and conventional spillways lies in the placement of aeration facilities. Conventional spillways feature a curved transition section that directly connects to the spillway. In contrast, the PSBS is equipped with a WES crest weir and a vertical sill of the same width, which converts supercritical to subcritical flow. This process strongly entrains air through hydraulic jumps at spillway entrances, thereby preventing cavitation damage. The study aims to experimentally investigate the flow regime, energy dissipation within the PSB, and the near-wall air concentration to ensure effective mitigation of cavitation damage downstream. The findings highlight the impact of the PSB on changing the jump type and relative local energy loss, influenced by the incoming Froude number, sill height, and sill length. Influenced by these factors, the variation in air concentration is crucial for reducing cavitation damage, necessitating potential adjustments in prototype applications to account for scale effects. Under such a pre-aeration approach, the air concentration along the downstream spillway warrants further investigation for the continuous optimization of the PSB’s design and its integration with spillways.